2011
DOI: 10.1103/physreve.83.051132
|View full text |Cite
|
Sign up to set email alerts
|

Condensate fluctuations of interacting Bose gases within a microcanonical ensemble

Abstract: Based on counting statistics and Bogoliubov theory, we present a recurse relation for the microcanonical partition function for a weakly interacting Bose gas with a finite number of particles in a cubic box. According to this microcanonical partition function, we calculate numerically the distribution function, condensate fraction and condensate fluctuations for a finite and isolated Bose-Einstein condensate. For the ideal and weakly interacting Bose gases, we compare the condensate fluctuations with those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It has been shown that the fluctuations of an interacting condensate, in the limit of large atom numbers, are up to two times smaller than the ones of the non-interacting gas [19]. The Bogoliubov approximation has been applied for the problem of fluctuations in the canonical [19][20][21][22][23][24] and then in the microcanonical ensemble [25,26]. However, this approach only holds for low temperatures and weak interactions.…”
mentioning
confidence: 99%
“…It has been shown that the fluctuations of an interacting condensate, in the limit of large atom numbers, are up to two times smaller than the ones of the non-interacting gas [19]. The Bogoliubov approximation has been applied for the problem of fluctuations in the canonical [19][20][21][22][23][24] and then in the microcanonical ensemble [25,26]. However, this approach only holds for low temperatures and weak interactions.…”
mentioning
confidence: 99%
“…is obtained through the exact microcanonical method [33]. We change the traditional MCE system with (N , V, E) to a closed system with (N , V, E(N , V, T )) to withdraw the adiabatic wall at t = 0 instantaneously.…”
mentioning
confidence: 99%
“…A prominent example is a quantum heat engine which may use an isolated finite system as its working substance to produce work [6]. In an isolated finite system [26] as well as quantum mechanics, the concept of energy (rather than temperature) is well-defined. Recently, a quantum-mechanical (QM) Carnot cycle working between two energy baths instead of heat baths has been generalized and studied intensively [10,13,27] since it was first proposed by Bender et al [9].…”
mentioning
confidence: 99%